Tax professionals’ views on continuing professional development (CPD) programs in Malaysia - Mat Udin, Noraza; Abdul Manaf, Nor Aziah; Ishak, Zuaini; A.R., Rusniza (2012)
This article reports on a study examining continuing professional development (CPD) programs for tax professionals.The aim of the study is to identify the important source of knowledge and the process of acquiring knowledge through CPD programs.Using a quantitative survey method, the views of CPD program participants were gathered.This study finds that CPD programs are no longer perceived as the main source of tax professionals’ knowledge enhancement.The ineffective programs lead tax professionals to search for knowledge through reading materials.Thus, this study suggests the needs to revise CPD programs in term of the contents and duration to re-attract tax professionals’ participation in the programs. By organizing suitable and effective CPD programs to the needs of tax professionals in various task environments, it is hoped that mismatch between the objective of CPD programs and tax professionals’ competencies is aligned.